Christian social workers and their sense of effectiveness in social work practice : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Social Work, School of Health and Social Services, Massey University, Albany Campus - Hare, Jennifer Lois (Massey University, 2010)
While social work roots are undoubtedly firmly in religious soil, over recent years the emphasis has widened to include a more inclusive definition of spirituality that seeks to mirror the diverse society we now live in. How social work responds to this increasingly complex environment is a matter of concern for social work educators, practitioners and academics, who all share the same aim of developing the most effective ways to deliver services to the client. The evidence-based practice movement is an evolving response, seeking to offer quality research based solutions to be implemented in practice. Missing in the equation to date is the ability to capture the spiritual aspects of practice both for practitioner (in terms of ‘use of self’) and client ( in relation to spiritual assets that assist them). To this end this qualitative study conducted semi-structured interviews with eight Christian practitioners as examples of spiritually motivated social workers. The research sought to explore how a Christian perspective contributed to a sense of effectiveness in social work practice. The findings produced discoveries that concurred with the literature and revealed insights from the participants about the ways in which they sought to practice that were consistent with their most valued beliefs. Using the findings and the literature, practical applications are suggested as a way forward for the inclusion of spiritual aspects in evaluating effective social work practice.
Keywords: Social workers; Social case work; Social services; Religious life; Christianity